2006
DOI: 10.1007/s11906-006-0024-9
|View full text |Cite
|
Sign up to set email alerts
|

Deranged energy substrate metabolism in the failing heart

Abstract: Control of energy metabolism in the heart is closely linked to cardiac performance. Dysregulation of energy-generating pathways occurs in many forms of heart disease, including heart failure. Uncertainty exists as to whether these alterations in the way adenosine triphosphate (ATP) is produced serve to protect the heart from excessive oxygen demands or have untoward long-term consequences. Regulation of fatty acid beta-oxidation (FAO), the principal source of ATP in the healthy heart, occurs at multiple levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Downregulation of FAO gene expression is a well-characterized response in the hypertrophied and failing heart, driven at least in part, by reduced PPARα-mediated transcriptional control of genes involved in fatty acid utilization. 20,5254 Second, the delivery of ketone bodies is increased in the failing heart (increased plasma concentration). Indeed, previous studies have shown that the mammalian heart is capable of avid ketone body uptake and oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of FAO gene expression is a well-characterized response in the hypertrophied and failing heart, driven at least in part, by reduced PPARα-mediated transcriptional control of genes involved in fatty acid utilization. 20,5254 Second, the delivery of ketone bodies is increased in the failing heart (increased plasma concentration). Indeed, previous studies have shown that the mammalian heart is capable of avid ketone body uptake and oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…A study determined human FA levels and found that although the FA oxidation rate increased, percentage of fatty acid oxidation amount was lower due to increased intake (31). Besides, acyl-CoA can accumulate in the cytoplasm if FA overload is imposed (32). Consistently, metabolomics analysis found that compared with non-T2DM patients, oxidation of long chain fatty acids in T2DM patients were incomplete, leading to significance increased plasma levels of C6, C8, C10, C12, and C14 (33).…”
Section: Discussionmentioning
confidence: 99%
“…Ketone bodies compete with other substrates in the heart, especially FA, to be used as fuel. This is particularly significant in the hypertrophied and failing heart, wherein there is down-regulation of FAO gene expression (Tian & Barger, 2006) and increased blood ketone bodies (Lommi, et al, 1996). The increase in ketone bodies is proportionate to the level of cardiac dysfunction and neurohumoral activation (Lommi, et al, 1996).…”
Section: Shift Of Metabolic Pathways In the Progression Of Heart Failurementioning
confidence: 99%